Active compounds present inRosmarinus officinalis leaves andScutellaria baicalensis root evaluated as new therapeutic agents for endometriosis - Ferella, Luciana (2018)
Research question: Can carnosic acid, (CA) rosmarinic acid (RA) and wogonin (WG) inhibit the growth of cultured human endometrial stromal cells and endometriotic-like lesions induced in a BALB/c model of endometriosis? Design: Primary stromal cell cultures were established from endometrial biopsies from women with endometriosis and controls. The human endometrial stromal cell line T-HESC was also used for in-vitro experiments. Endometriosis was surgically induced in BALB/c mice, which were randomly assigned to CA 2 mg/kg/day (n = 11); CA 20 mg/kg/day (n = 10); RA 1 mg/kg/day (n = 11); RA 3 mg/kg/day (n = 10); WG 20 mg/kg/day (n = 12); intraperitoneal vehicle control (n = 8) or oral vehicle control (n = 11). After surgery, CA and RA were administered intraperitoneally on days 14–28. WG was administered orally by intragastric gavage on days 14–26. Results: CA, RA and WG significantly inhibited in-vitro cell proliferation in primary and T-HESC cell cultures (P < 0.05). CA and WG induced cell cycle arrest of T-HESC at the G2/M phase (P < 0.01). RA reduced intracellular ROS accumulation (P < 0.001), whereas WG increased it (P < 0.05). WG significantly inhibited oestrogen receptor alpha expression in T-HESC (P < 0.01). In-vivo, CA, RA and WG significantly reduced lesions size (P < 0.05). All compounds significantly decreased the percentage of cells in proliferation (P < 0.05) whereas RA and WG further increased the percentage of apoptotic cells (P < 0.05) in endometriotic-like lesions. Conclusions: The results are promising; further investigation of these compounds as new therapeutics is needed.